The Ldybird illustrated thesaurus - Vickers, Clare; Massey, Peter, illus; Summers, Della, joint auth. (London : Ladybird)
When you've used the same word more than once - or you want just the riight word to express yourself -your thesaurus will give you all the help you need.
Keywords: English language -- Synonyms and antonyms; English language -- Synonyms and antonyms. -- Juvenile literature